2017
DOI: 10.3897/evolsyst.1.20172
|View full text |Cite
|
Sign up to set email alerts
|

Museum specimens as Noah’s Arc of lost genes. The case of a rhinoceros from Sumatra in the Zoological Museum Hamburg

Abstract: Understanding past and present genetic diversity, in particular in endangered species such as the rhinoceroses, is of paramount importance for a series of aspects in natural history, evolutionary systematics and conservation. As it turned out from several recent studies even in eminent museum specimens the historical context including its provenance often remains unresolved. At the same time modern molecular genetic techniques make this material more and more available also for integrative studies. With probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We found that morphological data on rhinos were available for the full range of species, demonstrating the potential of online images in morphological studies. Despite the low sample size, we were able to identify measurable morphological differences between species, largely driven by horn size, with black and white rhinos appearing more similar to each other than Indian and Javan rhinos, reflecting their closer evolutionary relationship (Glaubrecht & Neiber, 2017; Margaryan et al, 2020; Price & Bininda‐Emonds, 2009; Willerslev et al, 2009). Despite this, there was considerable overlap in morphology, reflecting real similarity in body proportions across rhino species.…”
Section: Discussionmentioning
confidence: 88%
“…We found that morphological data on rhinos were available for the full range of species, demonstrating the potential of online images in morphological studies. Despite the low sample size, we were able to identify measurable morphological differences between species, largely driven by horn size, with black and white rhinos appearing more similar to each other than Indian and Javan rhinos, reflecting their closer evolutionary relationship (Glaubrecht & Neiber, 2017; Margaryan et al, 2020; Price & Bininda‐Emonds, 2009; Willerslev et al, 2009). Despite this, there was considerable overlap in morphology, reflecting real similarity in body proportions across rhino species.…”
Section: Discussionmentioning
confidence: 88%